BIOMASS ENERGETIC POTENTIAL FROM TIMBER HARVESTING AT DIFFERENT TIMES OF STORAGE - Oro, Diego; Lopes, Eduardo Silva; Silva, Dimas Agostinho; Hillig, Everton; Pelz, Stefan Karl (Floresta, 2018)
This research aimed to characterize the energetic potential of chips of biomass residues from timber harvesting, stored outdoors in the field and indoors in the industry throughout different storage times, in order to improve the potential of the materials for energy generation. The study was performed in operational areas of a forestry company located in the Northeast region of the state of Santa Catarina, Brazil, in a Pinus taeda stand. Chips stored in the different storage types were evaluated at the times of 30, 60, 90, 120, 150, and 180 days, according to the following physical and chemical parameters: moisture content, calorific value, and ash content. Data were subjected to analysis of variance and to the Tukey’s post hoc means comparison test at 95% of probability. The results showed that the lowest moisture content was obtained in chips stored indoors for 60 days, whereas for chips stored outdoors the lowest moisture content occurred at 30 days. The chips stored outdoors for 30 days showed a higher calorific value of 4,792 Kcal.Kg-1, whereas chips stored indoors for 60 days had calorific value equivalent to the other storage times, 4,706 Kcal.Kg-1. Regarding the ash content, the best storage time for chips stored outdoors was 30 days, presenting an average ash content of 0.9%. Meanwhile, in the indoors storage, the ash content of the chips remained at low levels throughout the evaluated period. The indoor chip storage has proven to be the best option for use of biomass residues from timber harvesting for energy purposes.